Performance of CMS-Lines, R-Lines, Inbreds, Hybrids and Varieties of Sunflower Genotypes for Drought Tolerant Traits (London Journal of Research In Science: Natural and Formal, 2026)
Background: Sunflower (Helianthus annuus L.) is a vital oilseed crop known for its adaptability to diverse agro-climatic conditions. Drought stress, however, significantly limits its productivity. Previous studies have highlighted the importance of biomass partitioning and root traits in enhancing drought tolerance. Yet, comparative performance across different genetic groups-cytoplasmic male sterile (CMS) lines, restorer (R) lines, inbreds, hybrids, and varieties-remains underexplored.Objective: This study aimed to evaluate the drought tolerance potential of 48 sunflower genotypes, hypothesizing that hybrids and select parental lines exhibit superior root and biomass traits under water-limited conditions. The goal was to identify promising genotypes for breeding climate-resilient cultivars.Methods: A randomized complete block design (RCBD) was employed under controlled drought stress conditions. Eleven morphological and physiological traits were assessed, including root volume, root dry weight, root length, total dry matter (TDM), and specific leaf area (SLA). Statistical analyses included ANOVA for significance testing (P < 0.05), principal component analysis (PCA) to identify trait contributions, and biplot analysis for genotype clustering.Results: Significant genotypic variation was observed across all traits. Hybrids consistently outperformed other groups, particularly in TDM and root biomass. CMS-2B, CMS-104A, and IB-80 emerged as top-performing non-hybrids with robust root systems. Hybrids RSFH-1, KBSH-44, and KBSH-55 showed superior drought resilience. PCA revealed that PC1 accounted for 60% of the variance, dominated by TDM, root traits, and plant height, indicating overall plant vigor. PC2 (13.7%) captured the trade-off between leaf efficiency (SLA, SCMR) and structural resilience. Biplot analysis effectively grouped genotypes and highlighted promising paternal lines for drought-prone environments.Conclusions: The study underscores the value of multivariate analysis in identifying drought-tolerant sunflower genotypes. Hybrids demonstrated superior performance, while select CMS and inbred lines showed potential as breeding resources. These findings contribute to strategic cultivar development for water-limited regions, enhancing sunflower resilience and productivity.
Keywords: : CMS; drought; Hybrids; Inbreds; Root traits; Sunflower; Varieties